(untitled) (Pedagogy of Higher and Secondary Education, 2003)
The investigation specifies the linguo-stylistic analysis for world polys tylisticpattern of “great moral Text” made by one of the most talented poetesses of the ll-nd stage of Ukrainian national revival in Ukrainian Literature of the XX-th century Kostenko L. V.